The land grabbers of the Nacala Corridor - UNAC (GRAIN, 2015)
A new report by Mozambique's National Farmers' Union (UNAC) and GRAIN shows there is a colonial-style scramble for Africa's farm lands under way. Politically-connected companies based in offshore tax havens have grabbed hundreds of thousands of hectares of farmland from peasants in Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; Important; L - english / inglês; Northern PEA; law / direito

Development for Whom?: From the Case of the ProSAVANA Project in Mozambique – Master of Development Practice - Go Suzui
ProSAVANA project in Mozambique There are tremendous numbers of development projects all over the world. Mozambique is one of the least developed countries. A serious issue in Mozambique is food security. Even though 80 percent of the labor force in Mozambique engages in agriculture (USAID 2017), Mozambique’s farmland is tropical savanna that features very poor soil quality, and Mozambique does not have technologies to overcome this issue. As related to a food security issue, more than two out of five children under five years old are malnourished in Mozambique (UNICEF Mozambique 2017). The government of Mozambique decided to transform the current agriculture system and ensure food security. ProSAVANA is a triangular cooperation program among Mozambique, Brazil and Japan since 2009. The Japan International Cooperation Agency, the Japanese Ministry of Foreign Affairs and the Brazilian Cooperation Agency have participated in this project. The main purpose is to “improve the livelihood of inhabitants of the Nacala Corridor through inclusive and sustainable agricultural and regional development” and to “create employment through agricultural investment and establishment of a supply chain,” (ProSAVANA 2016). It seems that ProSAVANA has positive impacts on agriculture and on the total GDP of Mozambique and can improve childhood nutrition.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental